Waterfowl Censuses on Certain Reservoirs in Southern Illinois--1972-73 Through 1977-78 - Sanderson, Glen C. (1978)
not peer reviewed Open Restriction set for Item 123051 on 2022-04-15T21:21:09Z with date null by braxton@illinois.edu. Submitted by Susan Braxton (braxton@illinois.edu) on 2022-04-15T21:39:34Z No. of bitstreams: 1 19721978WaterfowlCensusSOILReservoirs.pdf: 31271318 bytes, checksum: 0328f72d65478c96cd0d09fdee781e44 (MD5) Made available in DSpace on 2022-04-15T21:39:34Z (GMT). No. of bitstreams: 1 19721978WaterfowlCensusSOILReservoirs.pdf: 31271318 bytes, checksum: 0328f72d65478c96cd0d09fdee781e44 (MD5) Previous issue date: 1978-07-06 unpublished Open